Teenage consumption of cleanliness: how to make it sustainable? - Kirsten Gram-Hanssen (Sustainability: Science, Practice, & Policy, 2007)
One third of all water and energy in Denmark, and in many other developed countries, is consumed directly in households. A significant part of this usage is related to cleanliness practices that are steadily changing toward more frequent showers and clothes washing. These trends will inevitably lead to still greater water and energy consumption. This article analyzes a set of in-depth interviews with teenagers and their parents to shed light on the cultural and social processes that shape cleanliness practices in the transition from child to adult. The conceptual perspective of this work is primarily predicated upon consumer theory that encompass modern and late modern consumption, conspicuous and ordinary consumption, and risk handling and hedonism in everyday life. Analysis shows that cleanliness practices are handed down from parents to children and also are subject to strong peer-group influence. Furthermore, the practices may involve considerations about risk handling in everyday life related to health issues. However, broader notions of sustainability are seldom reflected. The conclusion relates these insights to several policy questions.